Starvation- and antibiotics-induced formation of persister cells in Pseudomonas aeruginosa - Mlynarcik, Patrik; Kolar, Milan (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2017)
BACKGROUND: Planktonic stationary and exponential cultures of Pseudomonas aeruginosa are highly resistant to killing by bactericidal antimicrobials because of the presence of persisters, cells that are multidrug tolerant and play a key role in the recalcitrance of biofilm infections. AIM: The aim of this study was to investigate the formation of persister cells in P. aeruginosa stationary vs. exponential cultures using different class antimicrobials. METHODS: The susceptibilities of P. aeruginosa PAO1 wild-type and mutant strains to antimicrobials were determined by standard microtiter broth dilution method. In order to determine persister formation, dose- and time-dependent killing experiments were performed with antibiotics. RESULTS: Ceftazidime (Cephalosporin) showed little efficacy against either culture. Stationary-phase cells were more tolerant to imipenem (Carbapenem) than exponential cells, leaving a small fraction of persisters at high imipenem concentration in both populations. Polymyxin B (Polymyxin) appeared to be ineffective at low concentrations against both cell populations. Very high polymyxin B concentration completely eradicated exponential cells and regrowth was seen in a stationary population. Stationary cells were more tolerant to tobramycin (Aminoglycoside) than exponential cells but a higher concentration of tobramycin completely eliminated survivors. Ciprofloxacin (Fluoroquinolone) at a low concentration resulted in killing of both cultures of P. aeruginosa, producing persisters that were invulnerable to killing. CONCLUSIONS: Stationary cells appear to be somewhat more tolerant than exponential cells in all of these assays. We also showed that nutrient deprivation (serine starvation) regulated by stringent and general stress response, contribute to the increased tolerance of P. aeruginosa exponential and stationary planktonic cells via production of persisters.
Keywords: Dose-Response Relationship, Drug; tolerance; vztah mezi dávkou a účinkem léčiva; antimicrobials; Anti-Bacterial Agents; bakteriální léková rezistence; Drug Resistance, Bacterial; serin; persisters; planktonic; biofilmy; Microbial Sensitivity Tests; Serine; P. aeruginosa; Pseudomonas aeruginosa; Biofilms; mutant; antibakteriální látky; serine hydroxamate; mikrobiální testy citlivosti